2019
DOI: 10.1007/s10661-019-7244-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-driven variation in the removal of heavy metals from contaminated tailings leaching in northern Norway

Abstract: , conception and design, acquisition of data,analysis and interpretation of data, drafting the articale, revised and approved the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The positive effect of high temperatures in Cu dissolution from low-grade and concentrate ores were confirmed by other authors [10,34]. Fu and Lu [37] showed how the temperature plays an important role in the leaching of heavy metals from tailings. Furthermore, the effect of high temperatures on the leaching reactions can be explained by the Arrhenius Eq.…”
Section: Leaching Testssupporting
confidence: 64%
“…The positive effect of high temperatures in Cu dissolution from low-grade and concentrate ores were confirmed by other authors [10,34]. Fu and Lu [37] showed how the temperature plays an important role in the leaching of heavy metals from tailings. Furthermore, the effect of high temperatures on the leaching reactions can be explained by the Arrhenius Eq.…”
Section: Leaching Testssupporting
confidence: 64%
“…The leaching behavior has been known to be affected by operating conditions, e.g., temperature, pH, and reactivity or solubility between metal and liquid [35]. Since the leaching capacity and rate significantly increase as temperature rises [36], aerosols generated at higher temperatures induced by higher power are known to contain more metal elements. This study has the following limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that, compared to the initial stable heavy metal activities, the oxidation-reduction reaction in mine tailings led to an increase in Pb, Zn, and Mn activities by 42–69% (Trifi et al, 2019). In cold regions, the amounts of heavy metals leached in tailings increases with the increase in temperature (Fu et al, 2019). Kalinovic et al (2019) investigated the heavy metal contents in soil and found that wind direction had an important impact on the distribution of heavy metal pollution in soil and that the heavy metal contents in the soils that were in the path of the prevailing wind were higher.…”
Section: Discussionmentioning
confidence: 99%